Manajemen Tenaga Kependidikan dalam Meningkatkan Kinerja Tata Usaha pada Era 4.0 - Alfiyani, Nurul; suhatam, Suhatma; Mubarok, Amin (JIEM (Journal of Islamic Education Management), 2024)
Management of education personnel aims to utilize education personnel effectively and efficiently to achieve optimal results. The purpose of this research is to find out how to improve the performance of the administrative sector in the 4.0 era. The method used is a descriptive qualitative approach with data collection techniques in the form of interviews, observations, and documentation.The data analysis process is carried out with the stages of data collection, data reduction, data presentation and drawing conclusions. Based on this research the management of education personnel in improving the performance of the administrative field in the 4.0 era. Planning by analyzing employee needs in improving performance such as conducting employee training and development. Implementation in improving administrative perfomanace with development training and providing compensation. Evaluation in improving administrative performance in Nashuhiyyah junior high school is carried out once a month to find out how far the progress of employees in carrying out their duties and responsibilities.Keywords: Management of education personnel, administrative performance, in the era of 4.0AbstrakManajemen tenaga kependidikan bertujuan untuk mendayagunakan tenaga kependidikan secara efektif dan efesien untuk mencapai hasil yang optimal. tujuan penelitian ini adalah untuk mengetahui bagaimana meningkatkan kinerja tata usaha di era 4.0. Metode ini menggunakan pendekatan kualitatif deskriptif dengan menggunakan, wawancara, obsevasi dan dokumentasi sebagai teknik pengumpulan data. Proses analisis data dilakukan dengan tahapan pengumpulan data, reduksi data, penyajian data dan penarikan kesimpulan. Berdasarkan penelitian ini manajemen tenaga kependidikan dalam meningkatkan kinerja tata usaha di era 4.0 yaitu PerencanaanÂ  dengan menganalisis kebutuhan pegawai dalam meningkatkan kinerja seperti mengadakan pelatihan dan pengembangan pegawai. Pelaksanaan dalam meningkatkan kinerja tata usaha dengan pelatihan, pengembangan dan pemberian kompensasi. Evaluasi dalam peningkatan kinerja tata usahaÂ  di MTs Nashuhiyyyah dilakukan satu bulan sekali untuk mengetahui sudah sejauh mana perkembangan pegawai dalam melaksanakan tugas dan tanggung jawab nyaKata kunci : Manajemen Tenaga kependidikan, kinerja tata usaha, era 4.0